Report of the director-general - International Labour Organisation. African Regional Conference; International Labour Office (Paris : UNESCO, 1980)
"A single consolidated report covering the various topics to be considered by the Conference," prepared in advance of the conference by the International Labour Office.
A record of proceedings of the conference is published separately.
SERBIB/SERLOC merged record
Keywords: Conference papers and proceedings